1994
DOI: 10.1063/1.466468
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of water below 150 K

Abstract: Metastable liquid water, obtained by heating its hyperquenched glassy state above its glass→liquid transition temperature, crystallizes to cubic ice. Kinetics of this crystallization has been studied by Fourier transform infrared spectroscopy by determining the change in the spectra of stretching vibrations of the decoupled OD oscillator in 3.6 mole % HOD in H2O. The crystallization kinetics follows the equation x=[1−exp(−ktn)] and is diffusion controlled. Annealing at a temperature below its glass→liquid tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
137
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(155 citation statements)
references
References 12 publications
17
137
1
Order By: Relevance
“…In contrast with the broad absorption of the amorphous film, a clear peak at ∼2425 cm −1 (4.1 μm) is visible in the 150 K spectrum of crystalline ice. This band narrowing with growing temperature is consistent with previous literature measurements (Mayer & Pletzer 1985;Hague et al 1994;Dartois et al 2003) and was used by Hague et al (1994) for the study of the crystallization kinetics of water in hyperquenched glassy samples below 150 K. It can be rationalized in terms of the distribution of nearest neighbor oxygen-oxygen distances that is very broad for the cold amorphous samples (Madden et al 1978), but becomes much narrower with the decrease of local disorder induced by the temperature rise.…”
Section: Resultssupporting
confidence: 72%
“…In contrast with the broad absorption of the amorphous film, a clear peak at ∼2425 cm −1 (4.1 μm) is visible in the 150 K spectrum of crystalline ice. This band narrowing with growing temperature is consistent with previous literature measurements (Mayer & Pletzer 1985;Hague et al 1994;Dartois et al 2003) and was used by Hague et al (1994) for the study of the crystallization kinetics of water in hyperquenched glassy samples below 150 K. It can be rationalized in terms of the distribution of nearest neighbor oxygen-oxygen distances that is very broad for the cold amorphous samples (Madden et al 1978), but becomes much narrower with the decrease of local disorder induced by the temperature rise.…”
Section: Resultssupporting
confidence: 72%
“…Here, we ÿnd activation energy E ≈ 74 kJ=mol, which converts to a "fragility index" m = E=2:303RT g = 28 if we use T g = 136 K, or m = 24 if we use T g = 160 K, comparable to m for sodium trisilicate, a very strong liquid [39]. The value of E obtained agrees with that obtained experimentally by a standard analysis of the crystallization kinetics of vitreous water due to Haage et al [40] who reported the value 67 kJ=mol. Comparable values are reported by Smith et al [41] (84 kJ=mol) and Benniskens and Blake [42] (55 kJ=mol).…”
Section: Possible Consequences For Dynamic Behaviorsupporting
confidence: 79%
“…This spectral change is controlled by the crystallization of water ice (Hage et al, 1994) and suggests a close link between the H/D exchange and the morphological changes (see below).…”
Section: Processmentioning
confidence: 96%